Auditor demographic factors and dimensions of auditors’ skepticism in Jordan - Sayed Alwee Hussnie Sayed Hussin,; Norman Mohd Saleh,; Al-Smady, Ahnaf Ali (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this paper is to investigate the auditor demographic factors that can influence the level of skepticism dimensions in Jordan. One important contribution is it validates the skepticism dimensions in Jordan. Different from the majority prior studies on auditor skepticism, this study investigates auditors’ demographical factors that influence the level of skepticism dimensions. This study uses a survey approach on auditors in Jordan and received one hundred and twelve responses. Regression analysis was used to find relationships between demographic factors and skepticism dimensions. The result confirms that those who have experience with fraud is positively related to skepticism dimensions. The result could be driven by specific Jordanian context, such as business environment, business culture and political issues. Furthermore, the study is limited to Jordanian context. We cannot confirm the ineffectiveness of training in improving the dimensions of auditor skepticism because examination on training materials is not made and beyond the scope of this study.